Integrasi Analytic Hierarchy Process dan Goal Programming Dalam Pemilihan Pemasok - Annisa Kesy Garside; Martina Juan (Department Industrial Engineering, University of Muhammadiyah Malang, 2013)
Considering that raw material cost could reach 70% of product cost, supplier selection process was become important consideration to improve the efficiency of procurement department. The supplier selection process was multi-criteria problem involving qualitative and quantitative factors. UD Virgo Bersinar was one of fruit chips manufacturer located in Malang. The company often experienced shortage of jackfruits which interrupt production process. Thus, it was necessary to choose its supplier by considering company’s criteria and order allocation of selected supplier. This research would integrate supplier weight from Analytic Hierarchy Process and Preemptive Goal Programming model to determine priority of supplier and order quantity to the supplier. The model was formulated to achieve two objective functions, namely maximizing total value of purchasing and minimizing total cost of purchasing, by considering capacity of supplier and fulfillment of jackfruit. By running goal programming model, it was concluded that supplier from Semarang would supply 7.5 ton of jackfruit in November 2013-Januari 2014 and deficiency of needs would be supplied by supplier from Tajinan.